To determine the administrative act - Борбунюк, О. О. (Problems of legality, 2014)
Reveals the notion administrative act, the main theoretical and methodological approaches to the definition of an administrative act. Highlight a sign of an administrative act as a written document containes the rules of conduct of general direction.